If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 = 4x + -10 Reorder the terms: -35 = -10 + 4x Solving -35 = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -35 + -4x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 -35 + -4x = -10 + 0 -35 + -4x = -10 Add '35' to each side of the equation. -35 + 35 + -4x = -10 + 35 Combine like terms: -35 + 35 = 0 0 + -4x = -10 + 35 -4x = -10 + 35 Combine like terms: -10 + 35 = 25 -4x = 25 Divide each side by '-4'. x = -6.25 Simplifying x = -6.25
| 220=2.5(50)+b | | (3-w)(3w-1)=0 | | 3-5(n-4)=16 | | 3x+17=22 | | -0.3x+9.13=-0.1x+9.53 | | (2ab+2ab+2ab+2ab+2ab)+(7ab+7ab)+(5ab+5ab)+1ab= | | 3m=5-2m | | cosx=0.4166666667 | | x^2-19x+78=0 | | cosx=.4166666667 | | 5i/4-3i= | | G(2)=3x+5x-2 | | x^4+x^3-14x^2+6x-120= | | (2ab+2ab+2ab+2ab+2ab)(7ab+7ab)+(5ab+5ab)+1ab= | | x=0-3x | | 4+10z-1+5z+59=3z | | C(x)=800+5x^2 | | 4(3x-7)+6=8x-3(2-2x) | | 6[3+2]=15 | | 4(4m-3)=6 | | x=2-3x | | 6x^3+5x^2+x=0 | | 10a+8=4a | | 8=3(-3)+b | | 9x=6x-15 | | solve(3m-2)(9m+5)=0 | | x=-3-3x | | solve(3m-2)(9m-5)=0 | | (7ab+7ab)= | | d/dx=ln(729) | | 100x-0.12=300x+0.88 | | (5x)(-6)= |